Using the Concrete-Representational-Abstract Approach to Enhance Students’ Interest in Mathematics Refers to the Primer Mathematical Skills - Azmidar, Azmidar; Malasari, Putri Nur (Jurnal Pendidikan MIPA, 2022)
Students’ interest in mathematics is very influential to the achievement of learning outcomes, so the teacher is recommended to utilize the precise approach to enhance students’ mathematics interest. This study aims to analyze the achievement of mathematics students’ interest using the Concrete-Representation-Abstract (CRA) approach refers to primer mathematical skills. The study uses a quasi-experimental and a post-test design. The students in grade VII are the population in this study and use two groups were purposely selected, an experimental group that receives CRA and a control group that gets common learning (CL). The result shows that the mathematics interest’ of students who received the CRA approach is higher than students who only received CL. Refers to the indicator of students’ mathematics interest, the interaction with a teacher or friend to discuss the material scale gets the high score, and the lower score at the indicator diligently solving the assignment.Keywords: The Concrete-Representation-Abstract approach, mathematics interest.DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp894-903